Village governance based on e-governance in Melung Village, Banyumas District - Nurhamzah, Fachrizal (Gema Wiralodra, 2023)
This article aims to discover changes in the governance of public services in Melung Village, Banyumas Regency, as well as the implementation of E-Governance. In the Society 5.0 period, it was a human-centered and technology-based concept created from the development of the industrial revolution 4.0. Public services are making significant developments from post-Covid-19, where everything goes hand in hand with technology and big data. Implementation in Melung Village initially included a free internet network (wifi) and support from Kominfo. It implements village government services with an online model that uses a system based on the SDGs framework by converting paper-based to electronic. The official website of the Melung Village government already contains various types of village profile materials and several local government and central government sites, including Banyumas Regency Government, Banyumas Regency Communications and Information Office, Central Java Provincial Government. Ministry of Villages, PDT & Transmigration of the Republic of Indonesia, Ministry of Agriculture, Ministry of Home Affairs, Ministry of Telecommunications and Information, National Portal of the Republic of Indonesia, Wonderful Indonesia. Therefore, e-Governance-based village government in Melung Village, Banyumas Regency. This is expected to strengthen government institutions, significantly increase the village's scope, and meet development goals as set out in the SDGs. This study uses a literature review that analyzes village governance cases; the results indicate that Melung Village has been running well in village governance with evidence of changing paper based on electronics.